Comparison of Cooling Performance Between High Thermal Conductivity Steel (HTCS 150) and Hot Work Tool Steel (SKD 61) Insert for Experimental Tool Using Finite Element Analysis - Mohd Fawzi, Zamri; Zahari, Taha; A. R., Yusoff; Mohamad Farid, Mohamad Sharif; Mohd Ali Hanafiah, Shaharudin (Trans Tech Publications, Switzerland, 2014)
In hot stamping, the tool cooling system plays an important role in optimizing the process cycle time as well as maintaining the tool temperature distribution. Since the chilled water is forced to circulate through the cooling channels, there is a need to find the optimal parameters of the cooling channels that will cool down the tool efficiently. In this research paper, the cooling channel parameters that significantly influence the tool cooling performance such as size of the cooling holes, distance between the cooling holes and distance between the cooling holes and the tool surface contour are analyzed using the finite element method for both static and thermal analysis. Finally the cooling performance of two types of materials is compared based on the optimized cooling channel parameters.